Analysis of mortality from suicide in the Altai Republic, Russia, for the period of 1990-2019 - N. Semenova (European Psychiatry, 2022)
Introduction The Altai Republic (AR) is a national republic of the Russian Federation (RF), where the indigenous people – Altaians live, and where a high death rate from suicide is recorded.